Double-channel resistance-to-voltage converter for cable teraohmmeters - Yermoshin, N.I.; Yakimov, E.V.; Goldshtein, A.E. (KSU publ., 2020)
The paper considers a teraohmmeter resistance converter to monitor cable insulation with an additional input amplifier that emits a low-frequency interference signal. Adaptive algorithms for a double-channel converter circuit to compensate for low-frequency interference are proposed. There are considered algorithms usingnminimax criteria and linear approximation method for estimation of interference influence. It is shown classificationnof algorithms according to industrial frequency interference filtering method and signal observation interval. There were investigated two ways of interference application: step signal from a DC voltage source up to 300 V and fading harmonic signal from an AC voltage source and amplifier up to 300 V. A doublechannel circuit of the resistance-to-voltage converter is found to provide a 2-fold increase in the signal-tonoise ratio in comparison with a single-channel circuit. It is shown that the maximum deviation of readings for the single-channel circuit exceeds 20 % (up to 32 %) in short-term exposure to interference with amplitude of up to 300 V. At the same time, the maximum deviation for the double-channel circuit can attain 17 %, but it does not exceed 20 %. According to GOST 3345–76, the insulation resistance measuring error in the range of 10 GΩ to 100 TΩ should not exceed 20 %.The advantage of the proposed double-channel converter is the possibility to develop new algorithms to eliminate the dependence of readings on interference effects.
Keywords: insulation resistance; cable; interference; resistance-to-voltage converter; teraohmmeter